ANALISIS KOMPARATIF PENDAPATAN PETANI KELAPA SAWIT SWADAYA TERHADAP POLA KONSUMSI PADA UMUR TANAMAN PRODUKTIF DAN NON PRODUKTIF DI DESA SUNGAI RENGIT KABUPATEN BANYUASIN - Absharina, Aisyah; Lestari, Ratih (Agriculture Faculty of Flores University, 2025)
Palm oil is one of the plantation commodities that play an important role in the Indonesian economy. Banyuasin Regency is currently the largest supplier of palm oil. This study aims to analyze the contribution of independent palm oil income to the total revenue of farmer families in productive and non-productive crops, as well as to analyze the differences in farmer consumption patterns at the age of productive and non-productive crops in Sungai Rengit Village, Banyuasin Regency. This research was conducted in Sungai Rengit Village, Banyuasin Regency, from July 2021 to June 2022 using primary data collected through interviews using questionnaires. A total of 80 independent farmers, consisting of 40 productive and 40 non-productive crop farmers, were selected purposively. Data analysis was carried out using t-tests and descriptive statistics. The results of the study showed that the income of oil palm farmers was influenced by other business income. Farmers' consumption patterns show that farmers' welfare, both in productive and non-productive groups, is classified as prosperous based on the proportion of food and non-food consumption expenditure, where 40.49 percent of the portion is used for food needs and 59.51 percent for non-food needs. Meanwhile, oil palm farmer households with non-productive trees also have a balanced consumption mapping, with 40.86 percent used for food needs and 59.14 percent used for non-food consumption.